A CONCEPTUAL FRAMEWORK OF AGROPRENEURIAL INTENTION: INSIGHTS FROM MALAYSIAN HIGHER EDUCATION - Jaffery, Nur Shahafiqah Nadiah; Syed Annuar, Sharifah Nurafizah; Abd Rashid, Muhammad Hafiz (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Agriculture remains a vital sector in Malaysia, contributing significantly to food security, employment, and economic sustainability. However, the declining interest among graduates in agro-based ventures poses challenges to the sector’s long-term viability. Agropreneurship, which integrates entrepreneurial principles within agriculture, offers a promising solution to revitalize the industry through innovation and market-driven strategies. This paper develops a conceptual framework examining the influence of agropreneurial curriculum content, agropreneurship experiential learning, and perceived university support on agropreneurial intention, with perceived desirability and perceived feasibility acting as mediators. Grounded in entrepreneurial learning theory and institutional support theory, the proposed framework underscores the significance of structured education, practical exposure, and institutional backing in shaping graduates' aspirations to engage in agribusiness ventures. Recent statistics indicate that Malaysia recorded 1,030,020 agricultural holders, with 97.9% being individual agricultural holders, highlighting the need for entrepreneurial education to sustain the sector. Additionally, findings from the 2024 Agricultural Census suggest that modernizing agricultural education and support systems could enhance the feasibility of agropreneurial careers. By integrating these elements, this study offers insights into how higher education institutions can enhance agropreneurial competencies and encourage graduates to pursue careers in agro-based businesses. Future empirical research should validate the framework to measure its impact on graduates' entrepreneurial aspirations.